WOMAN PRODUCTIVE ROLE IN FISHERMAN HOUSEHOLDS (A CASE STUDY IN JEMBER) - Nurul Dwi Novikarumsari; Rokhani Rokhani; Sofia Sofia; Nurul Ulya Luthfiyana (Faculty of Animal and Agricultural Science, Diponegoro University, 2023)
Jember has large potential in fisheries. Fishery potential in Jember Regency which has an important role in the regional economy. The potential for sustainable capture of fish biological resources that have important economic value is 954,130 tonnes/year. Gender analysis in fisherman households is interesting for research related to fisheries productivity. This study aims to: 1) analyze reproductive and productive role in fisherman households in Jember Regency, 2) Analyze gender profiles in access and control over resources and institutions that support the improvement of traditional fishermen's welfare. Short-term efforts will formulate methods for fostering women in particular and traditional fishing families in general after going through a series of gender analysis. The research location was chosen purposively in Jember District which has fishery potential. The research approach used a qualitative approach. Data were collected through structured interviews, in-depth interviews, participatory observation and Focus Group Disscusion (FGD) in two village (Puger Wetan and Puger Kulon Village). The data analysis use Miles and Huberman and Harvard gender analysis. The result show that 1) the reproductive activities shows that the female household members carry out more reproductive activities than the male household members. The male household members do more productive activities than the female household members. In the division of labor, the percentage of time spent in productive activities is greatest for men in moderate time outlay, while women are in low time outpouring, 2) Control or decision making on productive activities is mostly carried out by the household members who carry out the activities. In agricultural activities, such as going to sea, repairing boats, and fixing/repairing nets, the dominant ones are carried out by men because men do a lot of these activities. While selling fish and non-agricultural activities (washing workers and trading) decision-making is carried out by women because women carry out activities.